Sabat Sebagai Tahun Perhentian Bagi Tuhan (Tinjauan Teologi Biblis Tentang Tanah Dalam Imamat 25:1-7 dan Implikasinya Bagi Masyarakat Batak) - Simanjuntak, Pahala Jannen; Sitanggang, Pintor Marihot; Sari, Monika Permata (NABISUK : Jurnal Teologi dan Pelayanan, 2024)
This article provides a theological explanation from the perspective of the Old Testament on how theological understanding of the Sabbath year. From the perspective of Old Testament theology, God is the only Creator of heaven, earth (land) and all its contents. Then humans are given the responsibility to cultivate and maintain all creations well. Because land has an important role in human life, land can actually be cultivated in such a way for the survival of creation. From the description of Old Testament theology, this article then develops an implication in Batak culture. In Batak culture, land is considered sacred because it is believed to be a gift from Debata Mulajadi Nabolon (DMN). Without land, humans cannot sustain their survival. The concept of the Sabbath Year (rest) in Leviticus 25:1-7 emphasizes the importance of rest for the land in order to realize that God is the owner of the land. It is a form of worship and has the same meaning in celebrations before God. In the New Testament (NT) Jesus said that God is the rest itself. Jesus emphasized that the Sabbath should not lose its true meaning and purpose, namely to be able to do diaconia.